Determinação dos alelos de grupos sanguíneos eritrocitários em doadores voluntários de sangue e medula óssea e pacientes politransfundidos da população Noroeste do Paraná, região Sul do Brasil. - Guelsin, Gláucia Andréia Soares (2010)
Blood red cell antigens are proteins linked to carbohydrates or lipids and are mainly expressed on red blood cells surface. The genes codify these antigens showing polymorphism that are mainly originated by point mutations, mainly the single nucleotide polymorphism (SNPs). The knowledge of Blood red cell antigens is essential for transfusion practice, since the antibody development against these antigens may lead to severe hemolytic situations, especially in hemoglobinopathy patients or any other diseases that depend on periodical transfusions. Classical hemaglutination is the mainly used technique in the detection of the different erythrocytic groups; however it presents some limitations, making it necessary the implementation of some other protocols to aid in the detection of these groups. Molecular biology may be a significant alternative in determining the antigenic profile and help in clarifying the molecular mechanisms involved in the diverse blood groups variables. Some genotyping protocols are already defined and validated for Brazilian population, however, it is necessary that some studies be done in the distinct Brazilian population. The aim of this study was to implement the molecular biology technique to investigate the polymorphism of some blood group genes in blood and bone marrow donors and polytransfused patients from the Northwest of Paraná, Southern Brazil and evaluate this population's genes polymorphism.